Expression and clinical value of CD105 in renal cell carcinoma based on data mining in The Cancer Genome Atlas - Shi, Donghui (Exp Ther Med, 2019)
The objective of the present study was to assess the expression of CD105 and its association with overall survival in three subtypes of renal cell carcinoma (RCC), namely clear cell (cc)RCC, papillary (p)RCC and chromophobe (ch)RCC. Data regarding the transcriptome and copy number of genes in RCC tumor samples and survival were obtained from The Cancer Genome Atlas. Bioinformatics analysis revealed that CD105 is overexpressed in ccRCC tumor tissue vs. normal renal tissue, and a higher CD105 copy number in ccRCC tissues was significantly associated with longer patient survival. The effect of the mRNA expression of CD105 in all three types of RCC and the copy number in pRCC and chRCC on patient survival was insignificant, but certain trends were observed. In addition, CD105 mRNA expression was associated with the metastasis and tumor stage, as well as pathological stage in ccRCC and pRCC. Pathway enrichment analysis revealed that CD105 may, through translation initiation of associated genes, promote RCC progression. The results of the present study suggest that in RCC tumors, the association of CD105 with different stages is complex. To evaluate the role of CD105 in RCC, its function should be assessed in addition to its expression. The exact influence of CD105 mRNA expression and copy number in RCC tumors on patient survival and the underlying mechanisms require further elucidation.